A C1q domain-containing protein in Pinctada fucata contributes to the innate immune response and elimination of the pathogen. Issue 131 (December 2022) - Wang, Jing; Thaimuangphol, Wipavee; Chen, Zhiwei; Li, Guiying; Gong, Xiaoqing; Zhao, Mingming; Chen, Zongfa; Wang, Bei; Wang, Zhongliang
Abstract: The C1q domain-containing proteins (C1qDCs) in bivalve mollusks primarily exist as the globular head C1q proteins (ghC1qs), for the N-terminal collagen domains were very rare in bivalves, although widespread in C1qDCs of vertebrates. In this work, the C1qDC protein with only a ghC1q domain (named as Pf-ghC1q ) was identified from Pinctada fucata, and molecular characterization, gene expression, and functional studies were also conducted. The full-length cDNA sequence of Pf-ghC1q was 738 bp long, containing a signal peptide of 23 residues encoded. Pf-ghC1q was clustered with some C1qDCs from other invertebrates in the phylogenetic tree analysis, rather than vertebrates. Pf-ghC1q was detected in all tested tissues, including the mantle, hemocyte, digestive gland, gill, and adductor muscle. Moreover, the expression levels of Pf-ghC1q were up-regulated in all tested tissues after the challenge with Vibrio alginolyticus 4 h later. The expression level of Pf-ghC1q was inhibited by specific si-276, and the low level of Pf-ghC1q affected the phagocytosis efficiency of V. alginolyticus by hemocytes. These results indicated that Pf-ghC1q may participate in the target recognition of V. alginolyticus and the phagocytosis process in the immune response of P. fucata . Highlights: The cDNA of a globular head C1q protein from Pinctada fucata was cloned and characterized. Pf-ghC1q was ubiquitous and highly expressed in gill and adductor muscle. Pf-ghC1q was responsive to Vibrio alginolyticus infection, and its expression level was highest at 2 h. Knockdown by specific siRNA suppressed the expression of Pf-ghC1q. Pf-ghC1q participated in the phagocytosis process and positively influenced phagocytic cells.